Revision of Tinospora (Menispermaceae - Chasmantheroideae - Burasaieae) in Singapore - Turner, I.M. (European Journal of Taxonomy, 2023)
The lianescent genus Tinospora Miers in Singapore is revised. Four species are recognised, two of which are newly described. Tinospora krispura I.M.Turner sp. nov. is known from Christmas Island and Singapore. Tinospora singapura I.M.Turner sp. nov. is known only from Singapore. Two new lectotypifications are included, one at the second step.